We have an equation with parentheses. To make our lives easier, first get rid of the parentheses. We do this by using the distributive property.
It is used like this: a(b + c) = ab + ac.
Use the distributive property on the left-hand side.
3(x - 1) = 6
3x - 3 = 6
Now we have an equation that is easier.
The x variable is being multiplied by 3 and added to -3.
Reverse all of these operations with their inverse operation.
3x - 3 = 6
3x = 9 <--- I got rid of the -3 term by using the inverse of subtraction. Addition.
And I did the same for both sides to keep the equation true.
x = 3 <--- The inverse of multiplication is division.
So, I divided both sides by 3.
So, x is equal to 3.
B is rational. B is the correct answer. B is rational.
-27 - (-3) = -27 + 3 = - 24
560 - 2(25 + 11) = 560 - 2(36) = 560 - 72 = 488
8y - x^2....x = -5, y = 4
8(4) - (-5)^2 =
32 + 5^2 =
32 + 25 =
57
Step-by-step explanation:
Hypotenuse = sqrt[(7)² + (11)²] = sqrt170 = 13m.